Employee Engagement and Job Satisfaction Among Part-Time and Full-Time Faculty Members : A Comparative Study in School of Business And Management Institut Teknologi Bandung - Haekal, Muhammad; Ginting, Henndy (Journal of Business and Management, 2019)
Abstract. Employee engagement towards an organization is one of the most important aspects to look after. It is one of the many factors that contributes to the overall performance of an organization considering how almost everything inside an organization is run by human resource (which includes part time faculty members). This research aims to define part-time and full-time faculty members’ job satisfaction level and condition, thereafter employee engagement. This paper is limited to only comparing and evaluating the satisfaction level of full-time and part-time faculty members of the School of Business and Management, Institut Teknologi Bandung, and focusing the analysis primarily towards factors that truly contribute to Minnesota Satisfaction Questionnaire’s job satisfaction and Gallup Q12, which will later determine overall employee engagement. The research participant is 40 people consisting of 29 part-time faculty members and 11 full-time faculty members and is conducted based on both primary and secondary data: primary being results based on circulating a 5-point Likert-scale questionnaire, and secondary being relevant information from online articles, websites, and offline references. This research will use Statistical Software for its analysis; T-Test to compare satisfaction and engagement between part-time and full-time faculty members, and Pearson Product-Moment Correlation Coefficient to find correlation between the two variables. The results indicates that there is a strong, positive correlation between Job Satisfaction and Employee Engagement level as where increases or decreases in satisfaction level were significantly related with increases or decreases in engagement level. Also, socio-demographic differences appeared to not have a significant impact on Faculty Members’ Job Satisfaction level, thereafter their Employee Engagement. The finding of this research is expected to help enhancing SBM ITB knowledge about their faculty members’ job satisfaction level, and be able to increase their engagement level. Key Words: Employee Engagement, Employee Satisfaction, Job Satisfaction, Part-Time, Faculty Member, Minnesota Satisfaction Questionnaire, Gallup Q12, Pearson Product-Moment Correlation Coefficient, T-Test, SPSS, School of Business and Management, Institut Teknologi Bandung